Infection following Anterior Cruciate Ligament Reconstruction: An Analysis of 6,389 Cases - Westermann, Robert; Anthony, Chris A.; Duchman, Kyle R.; Gao, Yubo; Pugely, Andrew J.; Hettrich, Carolyn M.; Amendola, Ned; Wolf, Brian R. (The Journal of Knee Surgery, 2017)
Infection following anterior cruciate ligament reconstruction (ACLR) is rare. Previous authors have concluded that diabetes, tobacco use, and previous knee surgery may influence infection rates following ACLR. The purpose of this study was to identify a cohort of patients undergoing ACLR and define (1) the incidence of infection after ACLR from a large multicenter database and (2) the risk factors for infection after ACLR. We identified patients undergoing elective ACLRs in the American College of Surgeons National Surgical Quality Improvement Program database between 2007 and 2013. The primary outcome was any surgical site infection within 30 days of surgery. We performed univariate and multivariate analyses comparing infected and noninfected cases to identify risk factors for infection. In total, 6,398 ACLRs were available for analysis of which 39 (0.61%) were diagnosed with a postoperative infection. Univariate analysis identified preoperative dyspnea, low hematocrit, operative time > 1 hour, and hospital admission following surgery as predictors of postoperative infection. Diabetes, tobacco use, age, and body mass index (BMI) were not associated with infection (p > 0.05). After multivariate analysis, the only independent predictor of postoperative infection was hospital admission following surgery (odds ratio, 2.67; 95% confidence interval, 1.02–6.96; p = 0.04). Hospital admission following surgery was associated with an increased incidence of infection in this large, multicenter cohort. Smoking, elevated BMI, and diabetes did not increase the risk infection in the present study. Surgeons should optimize outpatient operating systems and practices to aid in same-day discharges following ACLR.
Keywords: knee; sports; infection